A Dilemma about the Mental - Guy Dove (Institute of Philosophy of the Slovak Academy of Sciences, 2021)
Physicalism demands an explication of what it means for something to be physical. But the most popular way of providing one—viz., characterizing the physical in terms of the postulates of a scientifically derived physical theory—is met with serious trouble. Proponents of physicalism can either appeal to current physical theory or to some future physical theory (preferably an ideal and complete one). Neither option is promising: currentism almost assuredly renders physicalism false and futurism appears to render it indeterminate or trivial. The purpose of this essay is to argue that attempts to characterize the mental encounter a similar dilemma: currentism with respect to the mental is likely to be inadequate or contain falsehoods and futurism leaves too many significant questions about the nature of mentality unanswered. This new dilemma, we show, threatens both sides of the current debate surrounding the metaphysical status of the mind.